Sistem Pakar Pengendalian Pemberian Kredit Kendaraan Bermotor Menggunakan Metode Forward Chaining - Terisia, Vany; Yusuf, Diana; Arman, Shevty Arbekti (Jurnal Sistem Informasi (JUSIN), 2021)
Artificial intelligence is the goal of computer utilization. Artificial intelligence is often referred to as artificial intelligence. Artificial intelligence is a branch of computer science. Artificial intelligence can help humans make decisions, which can find more accurate information in other words making computers easier to use with natural displays to make it easy to understand. Basically, the credit application system aims to provide the right convenience and service according to customer needs, and also provides a guideline and conditions in the credit application clearly so that customers understand how the procedure in applying for credit. The risks faced by lenders are PT. Kb such as credit arrears or bad credit. Therefore, it takes the accuracy of the internal finance party in conducting analysis. In this case it can be used to study the Expert System with the Forward Chaining method and find solutions to the problems faced to find out whether the actions to be taken by internal parties in processing the provision of motor vehicle loans in accordance with its rules and provisions